2019
DOI: 10.1002/ente.201800946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicon Crystallite Size on Its Electrochemical Performance for Lithium‐Ion Batteries

Abstract: It is reported that silicon (Si) anodes with a smaller crystallite size show better electrochemical performance in lithium‐ion batteries (LIBs); Si particles with different diameters are also used. However, it is yet to be clarified whether the better performance is attributed to crystallite size or particle diameter. The effect of Si crystallite size on its anode performance using Si particles having the same diameter and different crystallite sizes is investigated. Longer cycle life is obtained for smaller c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 20 publications
(20 reference statements)
1
37
0
Order By: Relevance
“…Both works combined provided the upper and lower limit bounds for nano-Si particle size, based on sound interpretations of the physical phenomena here involved. A similar result was obtained in a different experimental work [ 96 ]. Nano-Si anodes of different particle sizes were cycled with increasing current rate, from 0.1 to 10 C. A large capacity fade was observed for Si electrodes with crystallite size equal to 30.9 nm, and results for smaller sizes suggest the same tendency.…”
Section: The Negative Electrode (Anode)supporting
confidence: 90%
See 1 more Smart Citation
“…Both works combined provided the upper and lower limit bounds for nano-Si particle size, based on sound interpretations of the physical phenomena here involved. A similar result was obtained in a different experimental work [ 96 ]. Nano-Si anodes of different particle sizes were cycled with increasing current rate, from 0.1 to 10 C. A large capacity fade was observed for Si electrodes with crystallite size equal to 30.9 nm, and results for smaller sizes suggest the same tendency.…”
Section: The Negative Electrode (Anode)supporting
confidence: 90%
“…Given the disadvantages of pure Si anodes, a successful design for a composite Si anode must target an increase in electrical conductivity, density, and chemical stability, besides being able to alleviate the mechanical stress induced by volume expansion. Since studies on composite Si anodes as a replacement to graphitic electrodes began, numerous designs combining nano-Si or SiO as active materials, with an outer matrix, most frequently carbon, have been proposed [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 ].…”
Section: The Negative Electrode (Anode)mentioning
confidence: 99%
“…Notably, the strong lattice reflections with a well crystalline nature are exhibited for NC1 nanostructures, which would benefit achieve high electrochemical performance. 38 In addition, the considerable presence of the metallic NiCo phase improves the electrical conductivity of the resultant composite materials. 33 Further, the calculated average crystallite sizes, by the Scherrer's equation, are found to be 27, 25, and 23 nm for NC1, NC2, and NC3 composites, respectively.…”
Section: Physical Properties Of Composite Materialsmentioning
confidence: 99%
“…It has been shown that the crystal size of Si also plays an important role in the cycle stability. [32,45] Although the sample prepared with NaCl possessed a smaller crystal size than the one prepared without NaCl, and their crystal size must have affected the cycle stability, their differences in particle size and morphology contributed more strongly. The electrochemical performance of both materials can be further improved with device fabrication strategies, such as carbon coating and preparation of composites with materials of high electrical conductivity.…”
Section: Discussionmentioning
confidence: 99%